PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS CANVA TERHADAP HASIL BELAJAR PKN SISWA KELAS III SD NEGERI I WONOKERSO - Rini Esti Rahayu; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of using Canva-based learning media on PKN learning outcomes for class III students at SD Negeri I Wonokerso. The research method used in this study was a Quasi-Experimental Posttest with a sample of 23 people. The sample in this study was taken using a simple random sampling technique. The data collection technique used was a multiple choice test with 20 questions. Based on the results of the study it can be seen that the significance value of 0 = 0.006 is smaller than alpha (α) = 0.05; with a tcount value of 3.226 and a ttable value of 1.672. It turns out that tcount > ttable or 2.889 > 1.674. This means that there is the effectiveness of Canva-based learning media on the learning outcomes of Civics in class III SD Negeri I Wonokerso.